Computational Simulations Identified Marine-Derived Natural Bioactive Compounds as Replication Inhibitors of SARS-CoV-2 - Kumar, Vikas; Parate, Shraddha; Yoon, Sanghwa; Lee, Gihwan; Lee, Keun Woo (Frontiers in Microbiology, 2021)
The rapidly spreading COVID-19 disease caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a worldwide community health emergency. Unfortunately, very less number of remedies were found effective till date against SARS-CoV-2 infection. Therefore, further research is required to achieve a lasting solution from this deadly disease. Repurposing available drugs and evaluating natural product inhibitors against target proteins of the SARS-CoV-2 could be an effective approach to hasten drug discovery and development. Aimed at this strategy, we derived Marine Natural Products (MNP)-based drug-like small molecules and evaluated them against three major target proteins of SARS-CoV-2 virus replication cycle. Drug-like database from MNP library was generated using Lipinski’s rule of five and ADMET descriptors. A total of 2033 compounds obtained and were subsequently subjected to molecular docking with 3CLpro, PLpro and RdRp. Docking analyses revealed that a total of 14 compounds displayed better docking scores than the reference compounds and significant molecular interactions with the active site residues of SARS-CoV-2 virus targeted proteins. Furthermore, the stability of docking-derived complexes were analyzed using molecular dynamics simulations and binding free energy calculations. Analyses revealed two hit compounds against each targeted proteins displaying stable behavior, binding affinity and molecular interactions. Our analyses revealed that identified hit compounds displayed potential in fighting with SARS-CoV-2 replication proteins, with good in silico pharmacokinetic properties, therefore can be considered for further in vitro studies.